Reconstruction of Theological Narrative: Integration of Local Wisdom into Religious Practices for Social Cohesion in Multicultural Societies of Southeast Asia - Akhsin Ridho; Aslam Sa'ad (Islam Transformatif : Journal of Islamic Studies, 2024)
This paper addresses the integration of local wisdom into theological narratives to enhance social cohesion in multicultural societies. The main question focuses on how religious teachings can adapt to local cultural values, making them more relevant and inclusive. Despite previous studies highlighting the benefits of this integration, a comprehensive analysis of its practical implications remains limited. This research contributes a novel perspective by systematically reviewing existing literature to establish patterns and themes that support social harmony through contextual theology. Using the Systematic Literature Review (SLR) method, the study identifies strategies, challenges, and outcomes of incorporating local traditions into religious practices. The findings of the study suggest that the adaptation of theological narratives to local cultures has the potential to improve social harmony and reduce tensions between groups. This integration also enriches religious practices, making them more inclusive and contextual according to the cultural characteristics of the local community. The conclusion of this study offers new insights into contextual theology in plural societies, where local wisdom plays a vital role in creating peace and social harmony.